Sweating: A Specific Predictor of ST-Segment Elevation Myocardial Infarction Among the Symptoms of Acute Coronary Syndrome: Sweating In Myocardial Infarction (SWIMI) Study Group - Gokhroo, Rajendra K.; Ranwa, Bhanwar L.; Kishor, Kamal; Priti, Kumari; Ananthraj, Avinash; Gupta, Sajal; Bisht, Devendra (Clinical Cardiology, 2016)
Background Today, cardiologists seek to minimize time from symptom onset to interventional treatment for the most favorable results. Hypothesis In the acute coronary syndrome (ACS) symptom complex, sweating can differentiate ST-segment elevation myocardial infarction (STEMI) from non–ST-segment elevation ACS (NSTE-ACS) during early hours of infarction. Methods This single-center, prospective, observational study compared symptoms of STEMI and NSTE-ACS patients admitted from August 2012 to July 2014. Results Of 12 913 patients, 90.56% met ACS criteria. Among these, 22.51% had STEMI. Typical angina was the most common symptom (83.82%). On stepwise multiple regression, sweating (odds ratio: 97.06, 95% confidence interval [CI]: 82.16-114.14, P < 0.0001) and typical angina (odds ratio: 2.72, 95% CI: 2.18-3.38, P < 0.001) had significant association with STEMI. For diagnosis of STEMI, positive likelihood ratio (LR) and positive predictive value (PPV) were highest for typical angina with sweating (LR: 11.17, 95% CI: 10.31-12.1; PPV: 76.09, 95% CI: 74.37-77.75), followed by sweating with atypical angina (LR: 3.6, 95% CI: 3.07-4.21; PPV: 50.61, 95% CI: 46.45-54.76), typical angina (LR: 1.05, 95% CI: 1.03-1.07; PPV: 22.97, 95% CI: 22.11-23.84), and atypical angina (LR: 0.77, 95% CI: 0.69-0.87; PPV: 18.09, 95% CI: 16.32-19.97). C statistic values of 0.859 for typical angina with sweating and 0.519 for typical angina alone reflected high discriminatory value of sweating for STEMI prediction. Conclusions Presence of sweating with ACS symptoms predicts probability of STEMI, even before clinical confirmation. Sweating in association with typical or atypical angina is a much better predictor of STEMI than NSTE-ACS.